2009
DOI: 10.1111/j.1365-2109.2009.02190.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary phospholipids on early ontogenesis of fish

Abstract: The aim of this paper is to provide explanations of how dietary phospholipid (PL) globally improves fish larval development, including growth and survival, digestive functions and skeletal development, and to propose optimal PL levels and sources in fish larval diets. Dietary incorporation of 8–12% PL related to dry matter (d.m.) promotes growth and enhanced survival in various species. Marine source PL, incorporating highly unsaturated fatty acids, was most efficient than soybean lecithin. This beneficial eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
79
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(82 citation statements)
references
References 66 publications
(99 reference statements)
3
79
0
Order By: Relevance
“…Surprisingly, despite numerous publications reporting the importance of dietary phospholipids for fish larvae, no studies have been published on the viability of SBL use as compared to ML containing diets in marine species. The efficiency of HUFA supplied through diet under the phospholipid form in sustaining growth, as exemplified in this study, is generally recognised [2]. However, the reasons for this are yet unclear.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Surprisingly, despite numerous publications reporting the importance of dietary phospholipids for fish larvae, no studies have been published on the viability of SBL use as compared to ML containing diets in marine species. The efficiency of HUFA supplied through diet under the phospholipid form in sustaining growth, as exemplified in this study, is generally recognised [2]. However, the reasons for this are yet unclear.…”
Section: Discussionmentioning
confidence: 92%
“…A dietary phospholipid source, particularly of marine origin, is generally recognised to promote growth and survival, as well as skeletal development, and perhaps stress resistance in fish larvae [1,2]. Phospholipids are key cell membrane constituents, and have a relevant role in lipid transportation from the intestine which seems to be of utmost importance in larvae; they are also thought to influence dietary palatability [1].…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial effects found were mainly associated with growth, survival rates, digestive functions, occurrence of deformities, and stress resistance in larval and juvenile stages of various species of fish Tocher et al, 2008;Cahu et al, 2009). Fish larvae appear to be dependent on a dietary supply of PL between 2-12% of the diet for normal growth and functional development (Tocher et al, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…As important part of cell membranes, PLs play a major role in maintaining the structure and function of membranes, as well as in the formation of cell organelles [127,128]. PLs also improve intestinal absorption of lipids by acting as emulsifiers in the chyme, as well as stimulating lipoprotein synthesis in enterocytes and lipid transport, reducing lipid accumulation in the intestine.…”
Section: Phospholipidsmentioning
confidence: 99%
“…PLs also improve intestinal absorption of lipids by acting as emulsifiers in the chyme, as well as stimulating lipoprotein synthesis in enterocytes and lipid transport, reducing lipid accumulation in the intestine. In addition, it has been suggested that PLs may improve diet quality by reducing the leaching of water-soluble micronutrients, acting as antioxidants, as well as feed attractants and providing choline, inositol, phosphorus and EFA that are essential for fish growth [127,128]. The optimal level of dietary PL supplementation depends on the species, developmental stage, culture conditions, and PL source [127].…”
Section: Phospholipidsmentioning
confidence: 99%